SEMIOTIKA KEPEMIMPINAN RANO KARNO: PENGGUNAAN TANDA BERBASIS BETAWI SENTRIS DALAM KAMPANYE PEMILIHAN KEPALA DAERAH - Mohammad Rifaldo Fajri; Virginia Meiske Ardiningrum; Jefri A Wempi (LPPM Stikosa - AWS, 2026)
The election of leaders in Indonesia has entered a new chapter since the implementation of the direct election system. Each candidate uses a political communication approach that focuses on increasing the electability of personalities associated with certain contexts. Rano Karno as one of the candidates for deputy governor of the Jakarta Capital Region uses signs attached to Betawi centrism. This research aims to understand the signs used by Rano Karno in the campaign for the election of regional heads, as well as to reveal the mechanisms and approaches used in utilizing Betawi cultural identity as a political force, and to understand how the signs are fabricated and amplified so that an active echo space is formed. The literature study used in this study is Leadership Semiotics which explains how signs are used to form certain images, how images are fabricated and amplified so that an active echo chamber is formed. In addition, a literature review on political and ethnic centric campaigns is also used. The method used in this study is qualitative constructivism with observational data collection techniques, interviews, and literature studies. The results obtained from this study are that Rano Karno as the creator of the sign forms the meaning of